Nonlinear Thermal Responses Outweigh Water Limitation in the Attenuated Effect of Climatic Warming on Photosynthesis in Northern Ecosystems. Issue 16 (19th August 2022) - Yin, Gaofei; Verger, Aleixandre; Descals, Adrià; Filella, Iolanda; Peñuelas, Josep
Abstract: Plant photosynthesis is strongly limited by temperature at high northern latitudes. The temperature sensitivity of plant photosynthesis in scenarios of future climatic warming, however, is highly uncertain. We used sun‐induced fluorescence—a satellite proxy for plant photosynthesis—to analyze the spatiotemporal response of photosynthesis to temperature at high northern latitudes. We detected a widespread decline in the sensitivity of photosynthesis to temperature during the last two decades: 3.25 versus 2.19%/°C, in the 2000s and 2010s, respectively. We used methods of machine learning and temporal composition to characterize the contribution of nonlinear thermal responses and water limitation. Both methods consistently identified the nonlinear thermal responses as the main driver of the attenuated positive warming effect. We highlighted the traditionally temperature‐limited ecosystems at high northern latitudes may be approaching the temperature tipping point, beyond which the warming effect on plant photosynthesis would transition from positive to negative. Plain Language Summary: Terrestrial plants absorb atmospheric carbon dioxide (CO2 ) by photosynthesis, which is a major mechanism mitigating climate change. Plant photosynthesis is strongly limited by temperature at high northern latitudes. Climate warming has decreased the temperature limitation on plant photosynthesis, and induced an increase in photosynthesis. Recent studies revealed a decline in the sensitivity of photosynthesis to temperature with ongoing warming. However, the underlying mechanism is still not clear. We used satellite‐observed sun‐induced fluorescence data to analyze the spatiotemporal response of photosynthesis to temperature at high northern latitudes. We confirmed the widespread decline in the temperature sensitivity of photosynthesis during the last two decades: 3.25 versus 2.19%/°C, in the 2000s and 2010s, respectively. We further provide compelling empirical evidence that the nonlinear thermal responses (direct effect of warming) outweighed water limitation (indirect effect of warming), accounting for this attenuated effect. We suggested that ecosystems at high northern latitudes are approaching the margin of the benefit of climatic warming. Key Points: The temperature sensitivity of photosynthesis significantly declined during the last two decades The nonlinear thermal responses of photosynthesis was the main driver of the attenuated positive effect of warming The temperature‐limited northern ecosystems may be approaching the temperature tipping point